From direct‐space discrepancy functions to crystallographic least squares. Issue 1 (14th November 2014) - Giacovazzo, Carmelo
<x xml:space="preserve">Abstract</x> Crystallographic least squares are a fundamental tool for crystal structure analysis. In this paper their properties are derived from functions estimating the degree of similarity between two electron‐density maps. The new approach leads also to modifications of the standard least‐squares procedures, potentially able to improve their efficiency. The role of the scaling factor between observed and model amplitudes is analysed: the concept of unlocated model is discussed and its scattering contribution is combined with that arising from the located model. Also, the possible use of an ancillary parameter, to be associated with the classical weight related to the variance of the observed amplitudes, is studied. The crystallographic discrepancy factors, basic tools often combined with least‐squares procedures in phasing approaches, are analysed. The mathematical approach here described includes, as a special case, the so‐called vector refinement, used when accurate estimates of the target phases are available.